2017
DOI: 10.1515/jim-2017-0087
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Bone Resorption Evaluation Around Single-piece Designed Bicortical Implants, Using Immediate Loading Protocol, Based on Orthopantomographs

Abstract: Background:Inserting dental implants in severely atrophied jawbones is a great challenge for the dental practitioner. There are an increasing number of patients who choose dental implantanchored prosthetic restorations despite compromised bone quality and quantity. There have been numerous attempts in adapting implant design for the atrophic crestal bone. One-piece, needle-type basal implant design is a typical design for these cases. These implants are inserted in the remaining compact bone located in the bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Regarding the maxilla and mandible, maxillary BMB height showed more resorption than that of the mandible during both the initial and functional periods. However, Szava et al reported that implants placed in the maxilla showed less bone loss than implants placed in the mandible after 1-year loading [35]. This result suggests that there are differences in remodeling procedures after GBR between the maxilla and mandible, and there may be greater volumetric shrinkage in the maxilla than in the mandible.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the maxilla and mandible, maxillary BMB height showed more resorption than that of the mandible during both the initial and functional periods. However, Szava et al reported that implants placed in the maxilla showed less bone loss than implants placed in the mandible after 1-year loading [35]. This result suggests that there are differences in remodeling procedures after GBR between the maxilla and mandible, and there may be greater volumetric shrinkage in the maxilla than in the mandible.…”
Section: Discussionmentioning
confidence: 99%
“…Among the advantages is the absence of microgaps between the implant platform and abutment, reducing vertical bone loss, which may occur at a slower rate with one-piece implants. [19][20][21] Furthermore, they could be used in restoring minimal edentulous spaces, and they allow for minimally invasive surgical procedures that foster improved soft tissue adhesion. 22 Numerous studies have explored the load distribution in one-piece and two-piece implants.…”
Section: Discussionmentioning
confidence: 99%